Optimum fodder-mulch allocation of tree foliage under alley farming in southwest Nigeria - Jabbar, M.A.; Cobbina, J. (Nitrogen Fixing Tree Association, 1992)
Previous economic analysis found alley cropping more profitable than coventional farming. One study that also compared alley farming with small ruminants found it less profitable than alley cropping. The present study shows, on the basis of more recent experimental data, that crop response to mulching is the most important determinant of whether or not the crop response to mulching, feeding part of the tree foliage to small ruminants is economically gainful, but at high crop yield levels and higher crop response to mulching, the use of pruning for feeding animals is uneconomic.